Peran Kualitas Layanan Dalam Menciptakan Loyalitas Mahasiswa - Dewa Nyoman Benni Kusyana; Putu Atim Purwaningrat; Milla Permata Sunny (UNHI Press, 2020)
Quality of service plays an important role in the world of education, especially higher education, although there is still debate about the position of students as customers, but it is believed that the quality of service in higher education plays an important role in ensuring the survival of a university. The purpose of this study was to determine the effect of higher education service quality on the satisfaction and loyalty of FEBP UNHI students. The model of higher education service quality used in this study is HEdPERF which consists of five dimensions namely academic aspects, non-academic aspects, reputation, access, and program issues. The sample used was 119 students from management and accounting study programs with simple random sampling technique, and the analysis technique used was path analysis. The results obtained were (1) HEdPERF had a positive but not significant effect on student loyalty, (2) HEdPERF had a positive and significant effect on student satisfaction, (3) satisfaction had a positive and significant effect on student loyalty, and (4) satisfaction mediated the effect of HEdPERF on student loyalty.